Moderating Effect of Psychosocial Safety Climate on the Association of Job Demands and Job Resources With Psychological Distress Among Japanese Employees: A Cross-sectional Study - Akiomi Inoue; Hisashi Eguchi; Yuko Kachi; Akizumi Tsutsumi (Safety and Health at Work)
Background: We examined the moderating (buffering or amplifying) effect of psychosocial safety climate (PSC) on the association of job demands (psychological demands) and job resources (job control, supervisor support, coworker support, and extrinsic reward) with psychological distress among Japanese employees. Methods: A self-report web-based questionnaire was administered to 2,200 employees (1,100 men and 1,100 women) registered with a Japanese private online survey company. The questionnaire included scales on job demands and job resources (the Job Content Questionnaire and the short-form Effort–Reward Imbalance Questionnaire), PSC (the 12-item PSC scale), and psychological distress (the K6 scale) and items on participants' demographic and occupational characteristics (age, gender, education, occupation, work form, and working hours per week). Hierarchical multiple regression analyses were performed using psychological distress as a dependent variable. Interaction terms of job demands and job resources with PSC were included. Results: There was a significant interaction effect of psychological demands with PSC on psychological distress (β = −0.053, p = 0.008), adjusted for demographic and occupational characteristics. Post hoc simple slope analysis showed that the simple slope of psychological demands was lesser at higher levels of PSC (1 standard deviation above the mean) (β = 0.101, p < 0.001) than at lower levels (1 standard deviation below the mean) (β = 0.199, p < 0.001). No significant interactions were observed between job resources and PSC. Conclusion: Our findings suggest that PSC buffers the positive association of psychological demands with psychological distress.